Climate change and rural institutions in Nepal - Hari Dhungana; Adam Pain; Dil Khatri; Niru Gurung; Hemant Ojha (Danish Institute for International Studies (DIIS), 2013)
This working paper provides a summary of initial findings on the factors influencing how meso-level institutions in Nepal are responding to climate change and extreme climate events. Nepal is still experiencing difficult processes of transition from war to peace. Underlying these difficulties and central to a view of Nepal as a state with limited capabilities is the ongoing challenge to its legitimacy, the failure of the state to perform in terms of delivery of basic public goods and reduce poverty, all underpinned by the persistence of an old political elite based on old social hierarchies and practices leading to enduring patterns of social exclusion. Through a combination of landscape features characteristic of mountainous countries, a largely subsistence agrarian sector, high poverty levels, and limited government capability Nepal has been ranked as the fourth most at risk country according to one Climate Change Vulnerability Index. Natural disasters - especially landslides and droughts in the mountains and hills and floods in the Terai - accentuated by extreme weather events are argued to be likely to have a significant impact on agricultural production and livelihoods, especially for marginal locations farmed by the more food insecure households. Although there is talk of climate policy integration or climate mainstreaming with assumptions of government coherence this is far from reality. The state and government are internally complex and incoherent, and the institutional landscape around climate change is complex both at national and district levels. Nepal's mountainous landscape makes it difficult to make wide generalizations about climate change impacts, risks and effects. Related to this, effects of climate-linked disasters and change may often, although not always, be localized and of small scale with respect to human impact in the mountains and hills although not in the plains. But the absence of a political settlement and the weakness of the state, a significant presence and influence of donors juxtaposed against a dynamic and increasingly contentious civil society leads to an extremely complicated, often muddled and context specific institutional landscape at all levels The climate change agenda has made inroads into policy processes and into the programmes and activities of the Government of Nepal entities and several donor agencies and service providers. Despite political contention and conflict, climate policy seems to have been supported by relevant government agencies. A significant part has been concerned to localise the climate change and disaster agenda and the development of policies. These still need translation into detailed policy and programmatic instructions for the meso-level government institutions. But policy development on climate change and disaster risk is mainly dictated and driven by donor agencies, and there is less ownership across various levels of governments. In some cases, government officers at the district level are even not aware of the plans that they themselves endorsed – indicating a co-option in climate change and disaster planning by donor-funded organisations who are keen to legitimize their own work through these plans.
Keywords: 300